Molecular dynamics simulations of ultrathin water film confined between flat diamond plates - Khomenko, A.V.; Prodanov, N.V. (Condensed Matter Physics, 2008)
Molecular dynamics simulations of ultrathin water film confined between atomically flat rigid diamond plates are described. Films with thickness of one and two molecular diameters are concerned and TIP4P model is used for water molecules. Dynamical and equilibrium characteristics of the system for different values of the external load and shear force are investigated. An increase of the external load causes the transition of the film to a solidlike state. This is manifested in a decrease of the diffusion constant and in the ordering of the liquid molecules into quasidiscrete layers. For two-layer film under high loads, the molecules also become ordered parallel to the surfaces. Time dependencies of the friction force and the changes of its average value with the load are obtained. In general, the behaviour of the studied model is consistent with the experimental results obtained for simple liquids with spherical molecules.